∫ 1 ∞ x 2 0 1 9 ln ( ln ( x ) ) d x = − C ln A + B γ
The equation above holds true for positive integers A , B , and C . Find min ( A + B + C ) .
Notation: γ denotes the Euler-Mascheroni constant
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution (+1).
Following you work, in general for any positive integer k > 1 ∫ 1 ∞ x k ln ( ln x ) d x = − k − 1 ln ( k − 1 ) + γ
Hey there @Hamza A , I believe it was Hummus A previously at least 4 years ago when I was active on this platform. We know from the definition of Gamma function that,
Γ ( a ) = 2 0 1 8 a ∫ 0 ∞ e − 2 0 1 8 x x a − 1 d x Differentiating both sides with respect to 'a' we have, 2 0 1 8 a Γ ( a ) ( ψ 0 ( a ) − ln ( 2 0 1 8 ) ) = ∫ 0 ∞ e − 2 0 1 8 x x a − 1 ln x d x Putting a = 1 along with ψ 0 ( 1 ) = − γ gives us, ∫ 0 ∞ e − 2 0 1 8 x ln x d x = − 2 0 1 8 ln ( 2 0 1 8 ) + γ Substitute e x → x to get, ∫ 1 ∞ x 2 0 1 9 ln ( ln x ) d x = ∫ 0 ∞ e − 2 0 1 8 x ln x d x = − 2 0 1 8 ln ( 2 0 1 8 ) + γ Therefore the answer is, A + B + C = 2 0 1 8 + 1 + 2 0 1 8 = 4 0 3 7
Slightly different solution, but using differentiation and the Gamma function:
I = ∫ 1 ∞ x 2 0 1 9 ln ( ln ( x ) ) d x
Substitute x = e u , d x = e u d u
I = ∫ 0 ∞ e 2 0 1 8 u ln ( u ) d u = d n d ∫ 0 ∞ e 2 0 1 8 u u n − 1 d u ∣ n = 1
Substitute t = 2 0 1 8 u
I = d n d 2 0 1 8 n 1 ∫ 0 ∞ e t t n − 1 d t ∣ n = 1
I = d n d 2 0 1 8 n Γ ( n ) ∣ n = 1
I = − 2 0 1 8 n Γ ( n ) ( ln 2 0 1 8 − ψ ( 0 ) ( n ) ) ) ∣ n = 1 = − 2 0 1 8 ln 2 0 1 8 − γ
Problem Loading...
Note Loading...
Set Loading...
I = ∫ 1 ∞ x 2 0 1 9 ln ( ln ( x ) ) d x
Let x = e u . Then d x = e u d u and:
I = ∫ 0 ∞ e − 2 0 1 8 u ln ( u ) d u
Let u = 2 0 1 8 t . Then d u = 2 0 1 8 d t and:
I = 2 0 1 8 1 ( ∫ 0 ∞ e − t ln ( 2 0 1 8 t ) d t )
I = 2 0 1 8 1 ( ∫ 0 ∞ e − t ln ( t ) d t − ∫ 0 ∞ e − t ln ( 2 0 1 8 ) d t )
I = − 2 0 1 8 1 ( − ∫ 0 ∞ e − t ln ( t ) d t + ln ( 2 0 1 8 ) ∫ 0 ∞ e − t d t )
The first integral is the definition of the Euler-Mascheroni constant , γ :
Then :
I = − 2 0 1 8 γ + ln ( 2 0 1 8 )
Thus:
A = 2 0 1 8 , B = 1 , C = 2 0 1 8 , A + B + C = 4 0 3 7